2020
DOI: 10.1186/s11689-020-09342-1
|View full text |Cite
|
Sign up to set email alerts
|

Translational outcomes relevant to neurodevelopmental disorders following early life exposure of rats to chlorpyrifos

Abstract: Background Neurodevelopmental disorders (NDDs), including intellectual disability, attention deficit hyperactivity disorder (ADHD), and autism spectrum disorder (ASD), are pervasive, lifelong disorders for which pharmacological interventions are not readily available. Substantial increases in the prevalence of NDDs over a relatively short period may not be attributed solely to genetic factors and/or improved diagnostic criteria. There is now a consensus that multiple genetic loci combined with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…In humans, UBE3A deletions cause Angelman syndrome characterized by severe developmental delay and intellectual disability, most notably lack of language acquisition [101]. Finally, we found that environmental risk factors associated with neurodevelopmental disorders, most notably early life exposure to the organophosphorus pesticide chlorpyrifos, reduced social approach behavior in response to 50-kHz USV playback [103]. Specifically, chlorpyrifos exposure led to a dose-dependent inhibition of social approach behavior, with the two highest doses completely blocking the social approach response in females but not males.…”
Section: Playback Of Ultrasonic Vocalizations In Ratsmentioning
confidence: 60%
“…In humans, UBE3A deletions cause Angelman syndrome characterized by severe developmental delay and intellectual disability, most notably lack of language acquisition [101]. Finally, we found that environmental risk factors associated with neurodevelopmental disorders, most notably early life exposure to the organophosphorus pesticide chlorpyrifos, reduced social approach behavior in response to 50-kHz USV playback [103]. Specifically, chlorpyrifos exposure led to a dose-dependent inhibition of social approach behavior, with the two highest doses completely blocking the social approach response in females but not males.…”
Section: Playback Of Ultrasonic Vocalizations In Ratsmentioning
confidence: 60%
“…At PND 38 ± 1, social play behavior was assessed following a protocol described previously ( Berg et al, 2018 , 2020a , b ). Each subject rat was placed with a freely moving, unfamiliar, strain-, sex-, and age-matched WT stimulus rat for 10 min in a clean, empty test arena (illuminated to ∼30 lux) containing a thin layer of clean bedding.…”
Section: Methodsmentioning
confidence: 99%
“…On PND 10, neonatal rats were assessed by collecting 40-kHz vocalizations made when isolated from the dam and littermates following a previously described protocol [ 16 , 50 , 60 , 61 ]. Rat pups were selected from the nest at random and placed in a small plastic container with clean bedding.…”
Section: Methodsmentioning
confidence: 99%